Cd34 and Mast Cell Analysis in Normal Oral Mucosa and Different Grades of Oral Squamous Cell Carcinoma: A Comparative Study - Kathuriya, Pargatsingh T (J Clin Diagn Res, 2015)
BACKGROUND: Oral Squamous Cell Carcinoma (OSCC) remains a serious health problem worldwide. Prognosis of OSCC is poor and long term survival rate still remains below 50%. Angiogenesis or neovascularisation plays an important role in tumour progression and metastasis. Mast cells have been implicated in promoting tumour angiogenesis, especially of digestive tract, little is known in OSCC. AIM & OBJECTIVE: To study the correlation between blood vessel density (BVD) and mast cell density (MCD) in different grades of OSCC. MATERIALS AND METHODS: Methods: Thirty eight paraffin blocks of different grades of OSCC were retrieved from the department and sections were stained with CD34 followed by counterstaining with toluidine blue. The slides were then analysed using Leica Software (Version 4.5). RESULTS: Mean BVD and MCD were found to be increased in OSCC as compared to normal mucosa. Increase in BVD with co-current increase in MCD was also observed in different grades of OSCC CONCLUSION: From our study, it was concluded that, mast cells play a major role in promoting tumour angiogenesis. But, as the grade of the tumour increases, other angiogenic factors may play a more significant role than mast cells in tumour progression.